Migratory and wintering behaviour of the Baltic Lesser Black-backed Gull (Larus fuscus fuscus) - Estrada,Joan (2025)
GPS tracking technologies are essential to follow long-distance migratory species throughout their annual cycle and identify the threats they encounter at large geographical scales. Information on the “lost” years of juvenile individuals of many species is lacking and it is vital to uncover their movements during these critical early stages. The Baltic Lesser Black-backed Gull (L. f. fuscus), a long-distance migratory seabird, is now classified as endangered and its populations have been decreasing in the last decades as a result of food shortages in the Baltic and pesticide contamination in its wintering grounds. A total of 70 adult and 39 young Baltic gulls from Swedish colonies were equipped with GPS trackers to compare the movement behaviour of adults versus juveniles in autumn migration, of adults in autumn versus in spring migration and of adults versus juveniles in their wintering grounds in Africa. This tracking data revealed that adults spent less time on migration and migrated at a faster speed than juveniles during autumn migration as a result of reduced time spent at stopovers. Adults also spent less time on migration and migrated at a faster speed during autumn migration than during spring migration due to the use of a shorter migration route, faster flight speeds and a reduced time spent at stopovers. Adults were also found to occupy larger core ranges and move larger distances within their wintering range than juveniles. Age differences in autumn migration speeds likely occur because juveniles achieve lower fuelling rates than adults at stopovers. Seasonal differences in adult migration may be a result of tailwinds encountered during autumn migration and headwind-driven detours in Africa plus a weather-dependent timed arrival at breeding grounds in spring. Previous knowledge on the wintering range landscape might facilitate the roaming of larger areas and distances in adults in winter compared to naïve juveniles. Our identification of the main wintering sites in Baltic gulls could provide support for the implementation of conservation actions tackling potential pesticide contamination in these areas. Further research on migratory connectivity and habitat use in wintering grounds is recommended to identify the specific contact zones between Baltic gulls and pesticides.